MENTRANSFORMASI ORGANISASI DENGAN MENGGUNAKAN CONGRUENCE MODEL: MENGANTISIPASI TUNTUTAN KEKINIAN ORGANISASI PEMERINTAH PUSAT DAN DAERAH - Haris Faozan (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2009)
The performance of institutional arrangement policy for central and local governments is said to be stagnant, or even tends to degrade from time to time. This condition is mainly because the design of organizational arrangement between central and local governments is not perceived as an immediate, basic need. This can be shown in the organizational arrangement that focuses merely on the organization shape, which is also considered insufficient. The emphasis on the organization formation is only related to the strategic organizational design, meanwhile the other important aspect, the operational design, is neglected. Another fundamental aspect neglected is the design of transformation process after the organization is formed. So far, the policy on formal arrangements ofgovernment organization, both for central and local governments, is not available yet. Therefore, the institutional transformation both central and local has never been route-mapped well, strategically unfocused, and often poorly performed. To overcome these problems, the institutional arrangement policy for central and local governments should be directed to the framework of 'organization as open system' in comprehensive and integrated way.